Prototyping Of Precission Farming Hydroponic Garden Using Arduino Using Design Thinking Method At Puriponic Greenhouse Depok - Tjahjono, Budi; Fauzia, Yunita; Kurnia, Ravie (International Journal of Science, Technology & Management, 2023)
This research discusses precision farming in hydroponic greenhouse using design thinking methods and sensors to ensure process control and monitoring in hydroponic greenhouse. The place of research was conducted at Puriponic Greenhouse Depok. During the Covid-19 pandemic there were social problems with many employee quarantines. Quaranitine occurs, activities are carried out at home, and there also many effect of unemployment. This will cause food problems for the community to be disrupted. This hydroponic system designs a system using an Arduino device with 6 sensors to control and monitoring hydroponic greenhouse. The methodology used is Design Thinking, the research time is 2022. The systems uses 6 sensors and 6 actuators. The result of this study are the design of hydroponic system prototype along with an actuator to guarantee hydroponic control and monitoring. The novelty of this system is the actuator of each sensor in guaranteeing control and monitoring of the greenhouse.